The Effect of Live Streaming and Discount on Impulsive Buying Instaperfect Cosmetics - Maharani, Alma Aria; Rachmawati, Dewi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Currently, many buying and selling transactions are conducted online. One promotional strategy is through live streaming. For individuals who want to buy a product through live shopping, most of them will aim to take advantage of discounts that will trigger impulsive behavior. This study aims to determine the effect of live streaming and discounts on consumer impulsive buying behavior for Instaperfect cosmetic products through the Shopee Indonesia e-commerce platform. This research method uses quantitative research and 100 respondents were selected by non-probability sampling and met certain criteria according to the Lemeshow formula. This study used validity tests, reliability tests and classical assumption tests, Correlation Tests, Multiple Linear Regression, Determination Tests, F-tests and T-tests. The results show that live streaming has a significant positive effect on impulsive buying. Then, discounts also have a significant positive effect on impulsive buying. The results also show that live streaming and discounts simultaneously have a significant effect on impulsive buying. This study provides theoretical implications, especially regarding the strengthening of the Stimulus-Organism-Response Theory and the concept of online marketing. Meanwhile, practical implications are useful for Instaperfect cosmetic products and similar products in their online marketing.